Cave lion: Isotopes and dietary paleoecology - Hervé Bocherens; Irina V. Kirillova (Earth History and Biodiversity)
The dietary preferences of Late Pleistocene cave lions in the mammoth steppe have been investigated using carbon and nitrogen isotopes of bone collagen. This study based on a review of published data and newly measured ones covers a wide area from Western Europe to Alaska and shows that reindeer was a preferred prey for most analyzed specimens, with some individuals in Western Europe and possibly in Urals showing a preference for cave bears as prey. The scattering of the isotopic data suggests a solitary way of life for cave lions, and competition with other predators such as cave hyena and brown bear, maybe less marked in Eastern Siberia where hyena was absent.